2014
DOI: 10.1093/mnras/stu2125
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Young Milky Way globular cluster Whiting 1 from near-infrared photometry

Abstract: Whiting 1 is a member of the fast-growing group of young globular clusters in the Milky Way halo. Preliminary estimates of its fundamental parameters have been provided using optical photometry and low resolution spectroscopy. In an attempt to strengthen our knowledge of Whiting 1, in this study we employ a complementary approach. Isochrone fitting method was applied on the Near-Infrared Color-Magnitude Diagram and yields an age t=5.7±0.3 Gyr, metallicity z=0.006±0.001 ([Fe/H]=−0.5±0.1) and distance modulus (m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…Whiting 1 is a 6 Gyr old Galactic GC that has been associated with Sgr because of its projected position, distance (d ∼ 30 kpc) and radial velocity (v r ∼ −130 km s −1 ), which are consistent with theoretical predictions for the stream in that region (Carraro et al 2007;Law & Majewski 2010b;Koposov et al 2012;Valcheva et al 2015). Forbes & Bridges (2010) have shown that this cluster fits in the age-metallicity relation followed by other globulars associated with Sgr.…”
Section: Introductionsupporting
confidence: 76%
“…Whiting 1 is a 6 Gyr old Galactic GC that has been associated with Sgr because of its projected position, distance (d ∼ 30 kpc) and radial velocity (v r ∼ −130 km s −1 ), which are consistent with theoretical predictions for the stream in that region (Carraro et al 2007;Law & Majewski 2010b;Koposov et al 2012;Valcheva et al 2015). Forbes & Bridges (2010) have shown that this cluster fits in the age-metallicity relation followed by other globulars associated with Sgr.…”
Section: Introductionsupporting
confidence: 76%
“…If Hydra I is a disrupting GC, then we expect it to contain (to first order) a single stellar population with the age of ∼ 5−6 Gyr as inferred from our stellar populations Hansen et al (2013), Valcheva et al (2015), and Rosenberg et al (1998a,b), respectively, are also included and labeled. As in Dotter et al (2011), individual analysis (Section 4.3).…”
Section: Is Hydra I a Disrupting Star Cluster?mentioning
confidence: 93%
“…The MW has few known, well studied GCs in the intermediate age (∼ 6−8 Gyr) range. These include Pal 1 (Rosenberg et al 1998a,b), Pal 12, Terzan 7 (Dotter et al 2010), Whiting 1 (Valcheva et al 2015), and 47 Tuc (Hansen et al 2013). With the exception of Whiting 1, all of these GCs have galactocentric distances 18 kpc (Harris 1996), similar to that of Hydra I (d MW = 19 kpc).…”
Section: Is Hydra I a Disrupting Star Cluster?mentioning
confidence: 99%
“…Spectroscopic, astrometric, and photometric observations have been undertaken with the aim of confirming, constraining, and ruling out the various proposed formation mechanisms of these multiple stellar populations (for an overview of the various proposals see the reviews of Charbonnel 2016; Bastian & Lardo 2018;Forbes et al 2018, and references therein). As the 'typical' clusters have not shown a clear path forward, there is now much interest in exploring the edges of the parameter space: the least massive clusters (e.g., Mucciarelli et al 2016;Simpson et al 2017b), the 'youngest' clusters (e.g., Valcheva et al 2014;Hollyhead et al 2016), and young massive clusters in other galaxies that are thought to be to precursors to the ancient globular clusters of the Milky Way (e.g., Cabrera-Ziri et al 2016, but see discussion in Renaud 2018Renaud , 2019 on whether these objects are truly analogues to present-day globular clusters). It is in this context that we have been investigating the very metal-poor globular cluster ESO280-SC06.…”
Section: Introductionmentioning
confidence: 99%